2016
DOI: 10.1177/2396987316678361
|View full text |Cite
|
Sign up to set email alerts
|

Optimal cut-off criteria for duplex ultrasound compared with computed tomography angiography for the diagnosis of restenosis in stented carotid arteries in the international carotid stenting study

Abstract: Introduction: Previous studies that reported duplex-ultrasound cut-off criteria, based on blood velocity parameters, for the degree of stenosis in a stented carotid artery were either retrospective, or the reference test was carried out only when a patient was suspected of having restenosis at duplex ultrasound, which is likely to have resulted in verification bias. We performed a prospective study of diagnostic accuracy to find new blood velocity cut-offs in duplex ultrasound for in-stent restenosis. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“… 17 , 18 However, in ICSS, a comparison was done of duplex ultrasound velocities and degree of restenosis determined by CTA in a subset of 103 patients treated with stents. 14 The optimum cutoff for peak systolic velocity in the internal carotid artery was greater than 1·25 m/s, which is similar to that used in our study for identifying moderate or higher (≥50%) restenosis. Hence, we used the same standardised velocity criteria in both treatment groups in this current analysis.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“… 17 , 18 However, in ICSS, a comparison was done of duplex ultrasound velocities and degree of restenosis determined by CTA in a subset of 103 patients treated with stents. 14 The optimum cutoff for peak systolic velocity in the internal carotid artery was greater than 1·25 m/s, which is similar to that used in our study for identifying moderate or higher (≥50%) restenosis. Hence, we used the same standardised velocity criteria in both treatment groups in this current analysis.…”
Section: Discussionsupporting
confidence: 62%
“… 13 No correction was made for the presence of a stent when measuring stenosis, based on the results of a study of a subset of patients treated with stents in ICSS, which showed similar estimates of stenosis severity from simultaneous CTA and duplex ultrasound examinations. 14 Ultrasound velocity measurements were not available from a few study centres; in these cases, we used the percentage stenosis reported by the local ultrasonographer and investigator. Additional carotid ultrasound and other imaging studies (eg, MRA or CTA) could be done if needed outside the regular follow-up intervals—eg, if patients had recurrent cerebrovascular events.…”
Section: Methodsmentioning
confidence: 99%
“…However, there is also no definition of such a deviation or correction factor for clinical Duplex in carotid stents. Some studies showed increased peak systolic velocities in the stent, [44][45][46] whereas others showed no difference 47 or stent-dependent deviations. 48 A large variance in contrast is visible in measurements 5A and 5C of the transmit voltage subcategory, with standard deviations of 1.25 and 1.59 dB, respectively (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…373,374 However, the need to use higher PSV thresholds for diagnosing >50% ICA restenoses after CAS was not confirmed in a recent substudy from ICSS. 375 DUS surveillance enables monitoring of disease progression in the contralateral ICA, which is more common than ipsilateral restenosis, with progression being dependent on disease severity at the time of CEA. The data are, however, conflicting as to its benefit.…”
Section: Recommendation 65mentioning
confidence: 99%